2022
DOI: 10.1186/s12969-022-00717-3
|View full text |Cite
|
Sign up to set email alerts
|

Bone remodeling serum markers in children with systemic lupus erythematosus

Abstract: Indroduction SLE is an autoimmune multisystem disease. Glucocorticoid is an irreplaceable medication for SLE. Glucocorticoid and inflammatory mediators impact bone remodeling by OPG/RANKL/RANK signal system, which could lead to osteoporosis. Our aim is to detect the expression of RANKL/OPG in children with SLE, and to preliminarily explore the changes of bone remodeling serum markers in children with SLE. Methods Serum RANKL and OPG of 40 children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
2
1
2
Order By: Relevance
“…Because only a tiny amount of serum RANKL may enter the systemic circulation and because some of the serum RANKL concentrations may come from nonskeletal sources, serum RANKL may not accurately reflect its level in the bone microenvironment [50], and this may explain why the current result did not record a significancy in serum level of SLE patients compared to healthy individuals. The current study disagrees with previous studies done by Hao et al, [51] and Ali et al, [52] who showed that RANKL was significantly higher in children with SLE. Another study done by Sandal et al, [53] on children with SLE found that RANKL levels were unrelated to disease activity.…”
Section: Serum Level Of Ranklcontrasting
confidence: 99%
“…Because only a tiny amount of serum RANKL may enter the systemic circulation and because some of the serum RANKL concentrations may come from nonskeletal sources, serum RANKL may not accurately reflect its level in the bone microenvironment [50], and this may explain why the current result did not record a significancy in serum level of SLE patients compared to healthy individuals. The current study disagrees with previous studies done by Hao et al, [51] and Ali et al, [52] who showed that RANKL was significantly higher in children with SLE. Another study done by Sandal et al, [53] on children with SLE found that RANKL levels were unrelated to disease activity.…”
Section: Serum Level Of Ranklcontrasting
confidence: 99%
“…The preferred therapeutic agent for SLE is glucocorticoids, which are rapidly and well effective in relieving clinical symptoms. The efficacy of glucocorticoids depends largely on the GRs [25] , which are members of the nuclear hormone receptor superfamily and can alter target genes, thereby modifying the effects of target cells and organs. In clinical treatment, many conditions require high-dose glucocorticoid therapy for effective control of disease progression, especially in critically ill patients, such as severe pneumonia, sepsis and other serious illnesses.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that long-term use of glucocorticoids can reduce osteoblast activity and increase osteoclast production, resulting in increased bone resorption, decreased bone formation, and a disruption of the bone remodeling balance, leading to bone loss, which progresses to osteoporosis after a certain degree of bone loss [9,10] . There are also research reports that the triad composed of osteoprotegerin (OPG), receptor activator of nuclear factor-KB (RANK), and receptor activator of nuclear factor-KB ligand (RANKL) is involved in the regulation of bone remodeling and is closely related to GIOP [11] . The current clinical treatment of GIOP mainly focuses on inhibiting bone resorption and promoting bone formation [12] .…”
Section: Introductionmentioning
confidence: 99%